Arsenic removal from synthetic waste water by CuO nano-flakes synthesized by aqueous precipitation method - Pal D.B.; Giri D.D.; Singh P.; Pal S.; Mishra P.K. (My University, 2025)
Arsenic contamination in the drinking water is a serious issue affecting health of inhabitants of developing countries like India and Bangladesh and needs cost effective solutions. The nanomaterials having large surface area per unit volume could be useful adsorbent for water arsenic decontamination. The CuO nanomaterial synthesized by aqueous precipitation method. The obtained nanomaterial suspension sonicated for 15 min before centrifugation at 5,000 g for 10 min. Thoroughly washed and overnight dried pellets at 60°C characterized by scanning electron microscope revealed nanoflakes structure of the pellets. The copper nanoflakes (CONF) have monoclinic CuO structure in XRD analysis. The kinetics of arsenic adsorption determined by varying arsenic content and dose of adsorbent for a period of 1 h revealed second order adsorption kinetics. The synthesized nano-flakes have potential application for arsenic removal from water well below safe limit. © 2017 Desalination Publications. All rights reserved.